Kaposis Sarcoma in HIV Positive Male (Journal of Bangladesh College of Physicians and Surgeons, 2015)
Kaposis sarcoma is a vascular tumor usually involves skin, mucous membrane and other organs. HIV associated Kaposis sarcoma is very rarely reported in Bangladesh. The reporting case was presented with a recurrent, ulcerated, firm nodule on left groin along with multiple blackish flat or raised lesions on different parts of body. According to previous histopathological report this case was operated as a case of recurrent fibrous histiocytoma and this time the diagnosis was confirmed histologically and by immunohistochemistry as Kaposis sarcoma. Later, it was found that the patient is serologically positive for HIV.J Bangladesh Coll Phys Surg 2014; 32: 164-166